Online business card / Linda Lim - Linda , Lim (2006)
Online Business Card is a web- it that offer the customer to design create and order the business card. The main idea of this project is to let the customer to design, create and order a business card of for themselves. Besides that, the customer also can upload the picture that they desire for developing or designing a business card for their own company. This system also provides the log-in system for the customer during customizing and payment process. The customer can create the business card by using any pictures and sentiments provided. The option, either they can start designing the business card by upload their own image or select any template that shown in this web-site. There are few advantages that are crucial ensure the success of this online Business Card of web-site. Most importantly, customer can create heir own desired business card by lower charges, provided log-in system and have many picture to select for designing the business card or the customer can upload the image that they want to design a business card. Besides that, it is also time-consuming for the businessman who very busy. They just have to create and order the business card by online. This report introduces the project and provides a description on the topics studied and searched during the literature survey. The Methodology for the system development is also discussed which is the waterfall with prototyping model. And finally, this report also included the system development tools chosen plus, the details of system designing of Online Business Card.